La simulazione tecnologica: Una questione linguistica nella sperimentazione teatrale italiana - Mango, Lorenzo (Mimesis Journal, 2015)
The essay is the historical and critical analysis of a season of the Italian New Theatre (from the ’70 to the beginning of the ’80) from a particular point of view: the use of technology. Not as presence of technological devices but the technology as metaphor, expression of a theatre who, founding its language on visual elements, elaborated a particular model of mixed media. Hence it follows the concept of “Technological Simulation” that has to be intended as simulation of the technology, as instrument for building a new model of stage writing.